Queer Communities and Activism in South Korea: Periphery-Center Currents. Issue 14 (5th December 2020) - Phillips, Joe; Yi, Joseph
ABSTRACT: Research into South Korea's LGBT+ communities is growing but still very limited, especially regarding communities in Busan and other urban areas outside the capital city, Seoul. We collected and analyzed responses from young LGBT+ who resided in the periphery and center and who described the two communities, their activist tactics, the connections/separations between them, and periphery-center characteristics of dialogue with opponents and participation in Korea's conservative, evangelical Christian churches. We reveal attitudinal and behavioral differences between Seoul and Busan (and other outlying areas), and we suggest that the differences reflect, in part, physical, social, and psychological distances between LGBT+ residing in the periphery and center. In time, outlying areas may converge with the center, imitating, though perhaps incompletely, Seoul's strong identity activism and more integrated community, or the periphery may pursue an independent, local identity.